PENGGUNAAN METODE BERMAIN PERAN DENGAN MEDIA AUDIO PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - mutiara ratu nirmala; Silvina Noviyanti; Zhafira Sayyidatunnisa; abiy dzaki edison (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to describe the use of role playing methods with audio media in social studies learning about ASEAN arts and culture for class V students. This research is a qualitative research type with a case study method. The data collection techniques used are observation, interviews, tests. The data analysis technique uses the case study method. The results of the research show that the use of role playing methods with audio media in social studies learning in class v elementary schools is effective. This is proven by positive learning outcomes such as students being more confident, able to control their emotions and having the courage to express opinions in social studies learning, especially on ASEAN arts and culture material. Each activity definitely has its own obstacles, such as lack of student involvement, a long time required, limited space and some students who are shy.